Facile Fabrication of Hybrid Carbon Nanotube Sensors by Laser Direct Transfer - Anca F. Bonciu; Mihaela Filipescu; Stefan I. Voicu; Thomas Lippert; Alexandra Palla-Papavlu (Nanomaterials, 2021)
Ammonia is one of the most frequently produced chemicals in the world, and thus, reliable measurements of different NH3 concentrations are critical for a variety of industries, among which are the agricultural and healthcare sectors. The currently available technologies for the detection of NH3 provide accurate identification; however, they are limited by size, portability, and fabrication cost. Therefore, in this work, we report the laser-induced forward transfer (LIFT) of single-walled carbon nanotubes (SWCNTs) decorated with tin oxide nanoparticles (SnO2 NPs), which act as sensitive materials in chemiresistive NH3 sensors. We demonstrate that the LIFT-fabricated sensors can detect NH3 at room temperature and have a response time of 13 s (for 25 ppm NH3). In addition, the laser-fabricated sensors are fully reversible when exposed to multiple cycles of NH3 and have an excellent theoretical limit of detection of 24 ppt.